Iron(II) complexes with N2O2 coordinating Schiff base-like equatorial ligand and 1, 2-bis(pyridin-2-ylethynyl)benzene as axial pincer ligand. (20th September 2019) - Schönfeld, Sophie; Lochenie, Charles; Hörner, Gerald; Weber, Birgit
Abstract: Three new unique mononuclear iron(II) pincer complexes were synthesized using 1, 2-bis(pyridin-2-ylethynyl)benzene as axially coordinating pincer ligand and N2 O2 coordinating Schiff base-like equatorial ligands. Magnetic susceptibility measurements reveal that all three complexes remain in the high spin state throughout the entire temperature range investigated. Reasons for this are restraining sterical interactions revealed in the single crystal x-ray structure analysis and extended DFT-computational studies of one of the pincer complexes. Those interactions also lead to the formation of unexpected side products during the synthesis such as a complex with two ethanol molecules as axial ligand, whose x-ray structure was determined.